(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
This article is dedicated to explain and analyse some of the similarities between two types of representation: dramatic representation, on one hand, and political representation, on the other. This analysis is carried out from the basis of the short essay “Histrionismo y representación”, published by Francisco Ayala in 1944. Besides, in line with the words of Ayala, there are some reflections about the present and the future of democratic political representation model.